Establishment of a new reference line for 2D transperineal ultrasound in urogynecology - Dionysopoulou, Anna; Skala, Christine; Weiss, Christel; Hasenburg, Annette; Albrich, Stefan (Clinical Journal of Obstetrics and Gynecology, 2020)
Background: The purpose of this study was to establish a new, reliable and reproducible reference line for assessing bladder neck descent using 2-dimensional transperineal ultrasound. Therefore, we created a novel line, named Symphysis-Levator Line (SLL) and defined it as the connecting line between the hyperechogenic, dorsocaudal edge of the symphysis pubis and the hyperechogenic anterior margin of the puborectalis muscle, posterior to the anorectal junction. Methods: A retrospective study was performed including 111 patients, who underwent a transperineal ultrasound as part of an urogynecological examination in the department of Urogynecology at the University Medical Center of the Johannes Gutenberg University Mainz. We calculated the bladder neck decent using the SLL and compared our results with the measurements assessed using a horizontal line through the infero-posterior margin of the symphysis pubis, as previously described by Dietz (Horizontal Symphysis Line, HSL). In addition, we calculated the intra- and interobserver reliability of the two methods and examined the influence of various patient characteristics on the obtained values. Results: Both methods demonstrated a high intra- and interobserver reliability. Even though the HSL produced slightly higher numerical values for the bladder neck descent, the novel SLL was more precise. Our data support that the 2-point fixation of the SLL on two anatomical structures ensures the stability of the reference plane during the functional changes of the pelvic floor. Conclusion: The Symphysis-Levator Line could be a useful tool for urogynecologists in the future.